Proposal of a New Analytical Procedure for Transverse Lamina Cracking in Multidirectionally Laminated Composites - ABE, Satoshi; KAGEYAMA, Kazuro; KATO, Tetsuji (Journal of the Japan Society for Composite Materials, 2002)
A new analytical method for calculation of transverse lamina cracking in multidirectionally laminated composites has been proposed in the present paper. Both energy balance criterion and stress criterion have been applied simultaneously for evaluation of initiation and extension of transverse lamina cracks with special consideration of residual stress. A micro model of [ θ/90 ] s laminate with a transverse crack in 90 deg. layer has been numerically analyzed and the results have been applied to evaluate the stress distribution and the stiffness reduction of a multidirectional laminate. Mixed mode fracture criterion based on Mode I and II energy release rates and Hashin's stress criterion were used to predict the initiation and extension of transverse lamina cracks in the multi layers. The analytical results were compared with experimental results of the cross-plied and quasi-isotropic laminates. Effects of ply thickness and stacking sequence on behavior of transverse lamina cracking were well explained by the present method. The present method has been expected to be a useful analytical tool for damage tolerance design of laminated composite structures.